Pembuatan pengawet alami nira kelapa aren melalui program KKN-PPM di Kecamatan Pujananting Kabupaten Barru - Firdaus W. Suhaeb; Taty Sulastry; Pince Salempa; Ernawati S. Kaseng (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The aims of community activities through trainingand outreach the KKN-PPM program, to increase society'sknowledge and skills in making natural preservative from theleaves of cloves. The method of implementation of trainingactivities and outreach is done through the methods oftechnology transfer, demplot (pilot project), andaccompaniment with the approach of the Partisipatory RuralAppraisal (PRA). The main target groups, i.e. the coconutpalm sugar Crafters and on Crafters Group of palm sugar.Being among the target group, i.e. the Group of farmers/women farmers, driving of PKK village, and teenage dropouts.Then the evaluation of the results of training and outreach,carried out on going evaluation and post evaluation. Theresults of the activities of the community shows that,implementation of training and outreach and mentoring in themanufacture of natural preservative from clove leaf throughthe KKN-PPM program, has been able to increase theknowledge and skills of participants training in the processingof natural resources available in district Pujananting. Thesuccess of training and outreach through the KKN-PPMprograms, looks also can encourage the growth of creativeideas and innovative and entrepreneurial souls trainee andvillagers during the KKN PPM program were execution.